Alternative protein consumption: A systematic review and future research directions. (10th March 2022) - Nguyen, July; Ferraro, Carla; Sands, Sean; Luxton, Sandra
Abstract: Marketing plays a critical role in addressing macro‐level societal problems, one of which relates to the reduction of meat consumption and increased consumption of alternative proteins. Such consumption practices are gaining attention given the rising concerns about food sustainability, safety, security, nutrition, and animal welfare. This paper provides a framework‐based systematic review of alternative protein consumption research, identifying relevant articles published between 2000 and 2020. Our framework combines the socio‐ecological model and capability, opportunity, and motivation model of behavior (COM‐B) to identify the various factors influencing alternative protein consumption. Antecedents – facilitators and barriers – of alternative protein consumption are organized, synthesized, and discussed using this combined model of behavioral influence. Our review outlines methodological approaches, identifies main variables of interest, highlights the opportunity for further theoretical development, and identifies gaps in research related to individual‐level opportunities and system‐level motivations. We conclude with theoretical, contextual, and methodological directions for marketing and consumer research to better understand and shape decisions and practices regarding the consumption of alternative proteins.